The Effect Of The Yanbu'A Method On The Success Of Reading-Writing The Qur'An By Students In Extracurricular Activities At Junior High School 31 Padang - Wira Kurnia Fitri; Jamaris Jamaris (Universitas Negeri Padang, 2022)
This research is motivated by the low ability to read and write Al-Qur'an students at SMPN 31 Padang City. The low ability to read and write the Qur'an of students is an inappropriate learning method. This study aims to determine the effect of the Yanbu'a method using teaching aids and books from volume 1 to volume 4 on the success of reading and writing the Koran by students in extracurricular activities at SMPN 31 Padang City. This study uses a quantitative method with a quasi-experimental approach with a one group pretest – posttest design. The population and sample of this study were all extracurricular students reading and writing the Qur'an. Meanwhile, data analysis used paired sample t-test. The results of data collection and processing carried out can be concluded, reading and writing the Qur'an of students before being given action (pretest) is categorized as low, the average pretest value of the sample is in the sufficient section. The students' reading and writing of the Qur'an after being given the action (posttest) was categorized as high because the average posttest value of the sample was in the good and very good part. There is a significant effect on students' reading and writing after being given an action (posttest) through the use of the Yanbu'a learning method because the paired sample t-test test sig 0.000 <0.05. In addition, the suggestion that researchers put forward is that it is better for the extracurricular learning process to read and write the Koran using appropriate learning media according to the needs of students, with the application of the yanbu'a method it should be one of the interesting and fun learning media. Keywords: Influence, Yanbu'a Method, Extracurricular